Clarification on Host Range of Didymella pinodes the Causal Agent of Pea Ascochyta Blight - Barilli, Eleonora; Cobos, Maria José; Rubiales, Diego (Frontiers in Plant Science, 2016)
Didymella pinodes is the principal causal agent of ascochyta blight, one of the most important fungal diseases of pea (Pisum sativum) worldwide. Understanding its host specificity has crucial implications in epidemiology and management; however, this has not been clearly delineated yet. In this study we attempt to clarify the host range of D. pinodes and to compare it with that of other close Didymella spp. D. pinodes was very virulent on pea accessions, although differences in virulence were identified among isolates. On the contrary, studied isolates D. fabae, D. rabiei and D. lentil showed a reduced ability to infect pea not causing macroscopically visible symptoms on any of the pea accessions tested. D. pinodes isolates were also infective to some extend on almost all species tested including species such as Hedysarum coronarium, Lathyrus sativus, Lupinus albus, Medicago spp., Trifolium spp., Trigonella foenum-graecum and Vicia articulata which were not mentioned before as hosts of D. pinodes. On the contrary, D. lentil and D. rabiei were more specific, infecting only lentil and chickpea, respectively. D. fabae was intermediate, infecting mainly faba bean, but also slightly other species such as Glycine max, Phaseolus vulgaris, Trifolium spp., Vicia sativa and V. articulata. DNA sequence analysis of the nuclear ribosomal internal transcribed spacer region (ITS) was performed to confirm identity of the isolates studies and to determine phylogenetic relationship among the Didymella species, revealing the presence of two clearly distinct clades. Clade one was represented by two supported subclusters including D. fabae isolates as well as D. rabiei with D. lentil isolates. Clade two was the largest and included all the D. pinodes isolates as well as Phoma medicaginis var. pinodella. Genetic distance between D. pinodes and the other Didymella spp. isolates was not correlated with overall differences in pathogenicity. Based on evidences presented here, D. pinodes is not specialized on pea and its host range is larger than that of D. fabae, D. lentil and D. rabiei. This has relevant implications in epidemiology and control as these species might act as alternative hosts for D. pinodes.